The complete mitochondrial genome sequence of Asclepios apicalis (Gerromorpha: Gerridae) - Liu, Yuxia (Mitochondrial DNA B Resour, 2021)
In this study, the complete mitochondrial genome of Asclepios apicalis was sequenced and assembled, which was first reported in Asclepios. The mitogenome of Asclepios apicalis was 15,391 bp in length, and it contained 22 transfer RNA (tRNA) genes, two ribosomal RNA (rRNA) genes, 13 protein-coding genes (PCGs), and a control region (D-loop), the overall base nucleotide compositions encoded was 42.9% A, 14.3% C, 10.0% G, and 32.8% T.